30‐1: Invited Paper: High Aspect Ratio OLED Microdisplay with Pin Mirror Lens for Small Form Factor AR Devices. Issue 1 (28th June 2021) - Kang, Chan-Mo; Shin, Jin-Wook; Choi, Sukyung; Kwon, Byoung-Hwa; Cho, Hyunsu; Cho, Nam Sung; Lee, Jeong-Ik; Kwon, Seungjoon; Lee, Hyunkoo; Park, Soon-Gi; Kim, Youngjoon; Ha, Jeonghun; et al.
Abstract : In this paper, we developed the high aspect ratio color OLED microdisplay and combined with the pin mirror lens, providing a wide FoV AR device in a small form factor. The white OLED exhibited the luminance of 14, 072 cd/m 2 and current efficiency of 33.8 cd/A at 9 V. To reduce optical crosstalk, color filters were directly patterned on the chip. The high aspect ratio OLED microdisplay was then combined with the pin mirror lens, resulting in maximum horizontal FoV 46.6° at the lens thickness of 4 mm. By using such a simple display module, we successfully demonstrated the small form factor AR device.